2012
DOI: 10.1002/chem.201201709
|View full text |Cite
|
Sign up to set email alerts
|

Direct Transformation of Simple Enals to 3,4‐Disubstituted Benzaldehydes under Mild Reaction Conditions via an Organocatalytic Regio‐ and Chemoselective Dimerization Cascade

Abstract: COMMUNICATIONScheme 4. A proposed reaction mechanism for the formation of benzaldehydes 2.Scheme 5. Transformation of two key intermediates 16 and 17 to benzaldehydes. In the proposed reaction mechanism, this involves Michaelaldol aromatization (see Scheme 4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The dimerized product was obtained in 58 % yield, and its structure was identified by NMR spectroscopy. The formation of this aromatized product for 2C occurs because of the transformation of the iminium ion to an enamine at room temperature …”
Section: Resultsmentioning
confidence: 99%
“…The dimerized product was obtained in 58 % yield, and its structure was identified by NMR spectroscopy. The formation of this aromatized product for 2C occurs because of the transformation of the iminium ion to an enamine at room temperature …”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, a 90% selectivity of p-MBA was obtained with a yield of 90% and a formation rate of 0.33 mmol p-MBA mmol cat. À1 h À1 , which is about six times of the report (using 2-butenal as reactants, Hong et al, 2006;Song et al, 2012). Notably, the ratio of p-MBA to o-MBA is up to 30 (see Table S1), which is more than two orders of magnitude higher than the literature (Moteki et al, 2016;Wang et al, 2019).…”
Section: Ll Open Accessmentioning
confidence: 62%
“…Organic amines, such as tetrahydropyrrole (THP) and its derivatives, could catalyze enals to yield p- methyl benzaldehyde derivatives ( Hong et al., 2006 , 2007 ; Song et al., 2012 ), although the reaction intermediates and mechanism have not been investigated. Furthermore, the system that can directly catalyze the self-condensation of acetaldehyde and then, aromatize enal intermediates to para -aromatic aldehydes has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Further study showed that an unprecedented organocatalytic Michael-aldol aromatization cascade occurred involving a dienamineiminium occurred in the reaction, without requiring an additional oxidant (Scheme 22). [49] In 2014, Sparr and co-workers reported a novel synthetic strategy for the atroposelective preparation of unsymmetrically substituted 1,1'-binaphthalene-2-carbaldehydes 108 by secondary amine-catalyzed (3 + 3) benzannulation (Scheme 23). [50] The experiments showed when the tertiary amine catalyst (such as MacMillan imidazolidinones) was used, the desired products were obtained in the absence of atroposelectivity, which suggested that competing general-base catalysis is operational.…”
Section: Secondary Amine-catalyzed Benzannulation Reactionsmentioning
confidence: 99%